Evaluation of Fresh Mushroom Compost in a Field Corn Production System. Issue 2 (2nd April 2020) - Coles, Phillip S.; Nogin, Galina; Fidanza, Michael; Roth, Greg
Abstract: Commercial mushroom producers are continually looking for new substrate raw material sources and pathways to dispose of mushroom compost (formerly called "spent mushroom substrate") after crop completion. A relatively new material used in the mushroom industry is corn stover, but supplies are somewhat limited. Corn farmers are often reluctant to remove stover from fields because of nutrient loss and possible soil erosion due to reduced soil protection, however, mushroom compost may be a potential substitute for stover. This field study evaluated the potential to improve corn crop yield and soil quality through stover removal coupled with the soil surface application of fresh mushroom compost. Stover was removed in amounts of 0, 70, and 100% and replaced with fresh mushroom compost at rates of 0, 5, 10, 20, and 40 tons per acre to find an optimal rate for both, and to provide a rationale to replace stover with mushroom compost in order to generate additional income for corn farmers, and increase substrate component availability and mushroom compost disposal alternatives, to the mushroom industry. The results showed that corn stover removal did not influence corn yield, but an increase in corn yield trend was observed with the application of an increasing amounts ≥ 20 tons fresh mushroom compost per acre. Analysis of soil parameters, at 0-2 inch and 2-8 inch rootzone depths, at the start of the field study compared to approximately one year later were mostly inconclusive. Of note, the addition of ≥ 5 tons fresh mushroom compost per acre resulted in an increase in soil pH at 0-2 inch depth.